(untitled) (Bangladesh Agronomy Journal, 2021)
The experiment was carried out at the Bangladesh Agricultural Research Institute, Gazipur during summer season of 2012 to identify suitable legume crops for growing with maize in a maize + legume intercropping system for better weed suppression, system productivity and economic benefits in kharif season. There were 17 treatments, viz.T1= Sole maize (no weeding), T2= Maize + Mungbean (no weeding), T3= Maize + Mungbean (weeding at 20 DAE), T4= Maize + Mungbean (weeding at 40 DAE), T5= Maize + Mungbean (weeding at 20 and 40 DAE), T6= Maize + Soybean (no weeding), T7= Maize + Soybean (weeding at 20 DAE), T8= Maize + Soybean (weeding at 40 DAE), T9= Maize + Soybean (weeding at 20 and 40 DAE), T10= Maize + Blackgram (no weeding), T11= Maize + Blackgram (weeding at 20 DAE), T12= Maize + Blackgram (weeding at 40 DAE), T13= Maize + Blackgram (weeding at 20 and 40 DAE) T14 =Sole maize (weed free), T15= Sole Mungbean (weed free), T16= Sole Soybean (weed free) and T17= Sole Blackgram (weed free) were studied. Intercropping systems significantly reduced the weed population and weed dry biomass in comparison to sole cropping of maize under unweeded situation. Among the three different intercropping systems, maize + mungbean with two hand weedings produced the lowest weed dry weight (184.30 g at 20 DAE and 14.07 g at 40 DAE) and the highest weed control efficiency (87% at 40 DAE) followed by maize + soybean and maize + blackgram intercropping systems. The highest grain yield was obtained from weed free sole maize (8.05 t ha-1) than unweeded sole maize (6.48 t ha-1) treatment. Among all intercropping, maize + mungbean along with two hand weedings gave the highest yield (maize: 7.18 t ha-1; 572.6 kg ha-1 mungbean), resource complementarity and profitability (MEY = 10.62 t ha-1, LER = 1.81 and BCR = 2.47). From the study it was concluded that maize + mungbean with two hand weedings at 20 and 40 DAE would be the best in reducing weed growth, producing maximum yield and getting net return in intercropping systems during kharif season. Bangladesh Agron. J. 2020, 23(2): 1-12